Sociability in a non-captive macaque population is associated with beneficial gut bacteria - Johnson, Katerina V.-A.; Watson, Karli K.; Dunbar, Robin I. M.; Burnet, Philip W. J. (Frontiers in Microbiology, 2022)
The relationship between social behaviour and the microbiome is known to be reciprocal. Research in wild animal populations, particularly in primate social groups, has revealed the role that social interactions play in microbial transmission, while studies in laboratory animals have demonstrated that the gut microbiome can affect multiple aspects of behaviour, including social behaviour. Here, for the first time, we explore behavioural variation in a non-captive animal population with respect to the abundance of specific bacterial genera identified from research on the microbiome–gut–brain axis. Social behaviour based on grooming interactions is assessed in a population of rhesus macaques (Macaca mulatta), and combined with gut microbiome data. We focus our analyses on microbiome genera previously linked to sociability and autistic behaviours in rodents and humans. We show in this macaque population that some of these genera are also related to an individual’s propensity to engage in social interactions. Interestingly, we find that several of the genera positively related to sociability, such as Faecalibacterium, are well known for their beneficial effects on health and their anti-inflammatory properties. In contrast, the genus Streptococcus, which includes pathogenic species, is more abundant in less sociable macaques. Our results indicate that microbes whose abundance varies with individual social behaviour also have functional links to host immune status. Overall, these findings highlight the connections between social behaviour, microbiome composition and health in an animal population.